THE ROLE OF DISCIPLINE IN INCREASING WORK COMMITMENT AND CREATIVITY, AND ITS IMPACT ON THE PERFORMANCE OF STATE CIVIL APPARATUS (ASN) IN THE REGIONAL SECRETARIAT OF NORTH TAPANULI DISTRICT - Panjaitan, Ferry; Panjaitan, Raya; Sitorus, Eben Ezer (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2025)
This research aims to test and determine the influence of discipline on work commitment and ASN work creativity, to test the influence of discipline on performance through work commitment and ASN creativity in the Regional Secretariat of North Tapanuli Regency through ASN creativity. This research also aims to determine the state of work discipline, work commitment, creativity and performance of ASN in the Regional Secretariat of North Tapanuli Regency through ASN creativity. The population in this research is all state civil servants who work at the Regional Secretariat of North Tapanuli Regency through ASN creativity, namely 110 people, and the entire population is used as respondents in this research or a saturated sample. This research shows that team member discipline is currently not very high, work commitment is not high, employees are still less creative and performance is still not optimal. Discipline does not have a significant influence on commitment, creativity or performance. ASN work commitment does not significantly affect performance, but ASN creativity has a positive and significant effect on performance. Indirect testing shows that discipline significantly affects performance through the work commitment of ASN of the North Tapanuli Regency regional secretariat. In contrast, discipline does not significantly affect performance through the creativity of ASN of the North Tapanuli Regency regional secretariat.